Use Behavior Analysis Of Job Seekers Using The E-Recruitment System In The Special Region Of Yogyakarta - Muhammad Fakhrurrozi; Muafi Muafi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
E-Recruitment is a job search platform for job seekers. In the modern era, organizations adapt human resource recruitment systems to remain viable. Where the success of e-recruitment depends on the large number of uses of the e-recruitment platform and the organization getting competent human resources. The aim of this research is to determine the influence of performance expectancy, effort expectancy, social influence, facilitating conditions on behavioral intention, and behavioral intention on the use behavior of job seekers using e-recruitment in the Special Region of Yogyakarta. This type of research is quantitative descriptive, namely research that uses mathematical models, theories and/or hypotheses related to natural phenomena. The sample in this study used a purposive sampling technique, where the sample population in the Special Region of Yogyakarta was 210 job seekers who had used e-recruitment. Based on the results of research conducted by researchers in the Special Region of Yogyakarta, what was found was that performance expectancy, effort expectancy, social influence, facilitating conditions together have a significant influence on behavioral intention, and behavioral intention influences the use behavior of job seekers using e- recruitment in the Special Region of Yogyakarta with a p value < 5%, meaning that if performance expectancy, effort expectancy, social influence, facilitating conditions increase, interest in using e-recruitment will also increase, and the higher the level of behavioral intention, the use of e-recruitment behavior will also increase.